Church-Based Social Support and Religious Coping - Krause, Neal; Ellison, Christopher G.; Shaw, Benjamin A.; Marcum, John P.; Boardman, Jason D. (Journal for the scientific study of religion, 2001)
The purpose of this study is twofold: to explore the nature of church-based social support, and to see whether support received in religious settings is related to the use of religious coping methods. The data come from a nationwide survey of members of the Presbyterian Church USA. Three dimensions of religious support are examined in detail: emotional support from church members, spiritual support from church members, and emotional support from the pastor. These dimensions of support are used to evaluate an issue that has been largely overlooked in the literature--the relationship between religious support and religious coping. The findings reveal that people are especially inclined to use positive religious coping responses when they receive spiritual support from church members. Even though emotional support from the pastor also increases the use of religious coping methods, the relationship is not as strong. Finally, emotional support from church members has no effect.